Vacuum System and Modeling for the Materials Plasma Exposure Experiment. (17th November 2017) - Lumsdaine, Arnold; Meitner, Steve; Graves, Van; Bradley, Craig; Stone, Chris; Lessard, Timothy; McGinnis, Dean; Rapp, Juergen; Bjorholm, Tom; Duckworth, Robert; Varma, Venugopal
Abstract: Understanding the science of plasma-material interactions (PMI) is essential for the future development of fusion facilities. The design of divertors and first walls for the next generation of long-pulse fusion facilities, such as a Fusion Nuclear Science Facility (FNSF) or a DEMO, requires significant PMI research and development. In order to meet this need, a new linear plasma facility, the Materials Plasma Exposure Experiment (MPEX) is proposed, which will produce divertor relevant plasma conditions for these next generation facilities. The device will be capable of handling low activation irradiated samples and be able to remove and replace samples without breaking vacuum. A Target Exchange Chamber (TEC) which can be disconnected from the high field environment in order to perform in-situ diagnostics is planned for the facility as well. The vacuum system for MPEX must be carefully designed in order to meet the requirements of the different heating systems, and to provide conditions at the target similar to those expected in a divertor. An automated coupling-decoupling ("autocoupler") system is designed to create a high vacuum seal, and will allow the TEC to be disconnected without breaking vacuum in either the TEC or the primary plasma materials interaction chamber. This autocoupler, which can be actuated remotely in the presence of the high magnetic fields, has been designed and prototyped, and shows robustness in a variety of conditions. The vacuum system has been modeled using a simplified finite element analysis, and indicates that the design goals for the pressures in key regions of the facility are achievable.